Implementasi Time Lock Auto Decryption Untuk Keamanan Surat Wasiat Digital Berbasis Web dan Mobile - Gemasih, Reza; Romli, Moh. Ali (TIN: Terapan Informatika Nusantara, 2025)
The management of wills in Indonesia still relies heavily on physical documents stored by notaries or family members. This manual approach presents several weaknesses, including the risks of damage, loss, forgery, and unauthorized access before the intended time. To address these issues, this study develops a digital will-security system utilizing a combination of AES–RSA encryption and a server-based Time-Released Cryptography (TRC) mechanism. AES is employed to encrypt document contents quickly and efficiently, while RSA secures the AES encryption key. TRC is implemented to ensure that the decryption process can only be performed at the predetermined time, thereby systematically preventing unauthorized access. This research adopts the Waterfall model, encompassing requirement analysis, system design, implementation, and performance and security testing. The test results show that the average encryption time for a 300 KB document is 125 ms, while the average decryption time is 118 ms. The TRC mechanism demonstrates 100% timing accuracy with no deviation from the release schedule, and all attempts to access the document before its designated time failed completely (0% success rate). The integration of AES–RSA and TRC proves effective in enhancing security, maintaining confidentiality, and controlling timely access to digital will documents.